2014
DOI: 10.1371/journal.pone.0099662
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Road Traffic Incidents in Peru 1973–2008: Incidence, Mortality, and Fatality

Abstract: BackgroundThe epidemiological profile and trends of road traffic injuries (RTIs) in Peru have not been well-defined, though this is a necessary step to address this significant public health problem in Peru. The objective of this study was to determine trends of incidence, mortality, and fatality of RTIs in Peru during 1973–2008, as well as their relationship to population trends such as economic growth.Methods and FindingsSecondary aggregated databases were used to estimate incidence, mortality and fatality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
2
6
1
2
Order By: Relevance
“…15 In addition to confirming findings that males, rural residents, and older adults are at higher risk of road traffic mortality compared with females, urban residents, and younger people, 33,34 our study identified urban-rural and provincial disparities in mortality and mortality changes in China. These findings, which match reports concerning urban-rural and within-country disparities from the USA, 35 Peru, 36 and India, 37 could reflect a combination of risk factors in rural areas and underdeveloped provinces. These factors include poor road infrastructure and road traffic control, lagging economic development, lower quality of prehospital trauma aid and hospital treatment, different commuting methods, diverse population density, different policies for road traffic management (eg, the Chinese Government prohibited riding motorcycles in most large and medium-sized cities but encouraged automobiles and motorcycles in rural areas from 2009 to 2013), 38,39 but also less stringent road traffic policies and enforcement, and comparatively frequent law violations and risky behaviours.…”
Section: Discussionsupporting
confidence: 89%
“…15 In addition to confirming findings that males, rural residents, and older adults are at higher risk of road traffic mortality compared with females, urban residents, and younger people, 33,34 our study identified urban-rural and provincial disparities in mortality and mortality changes in China. These findings, which match reports concerning urban-rural and within-country disparities from the USA, 35 Peru, 36 and India, 37 could reflect a combination of risk factors in rural areas and underdeveloped provinces. These factors include poor road infrastructure and road traffic control, lagging economic development, lower quality of prehospital trauma aid and hospital treatment, different commuting methods, diverse population density, different policies for road traffic management (eg, the Chinese Government prohibited riding motorcycles in most large and medium-sized cities but encouraged automobiles and motorcycles in rural areas from 2009 to 2013), 38,39 but also less stringent road traffic policies and enforcement, and comparatively frequent law violations and risky behaviours.…”
Section: Discussionsupporting
confidence: 89%
“…Such sex difference could be probably explained by the fact that men would be more exposed to risk factors, such as more driving and time spent on road. As consistent with observations from other settings (Lee, et al, 2014;Miranda, et al, 2014), the elderly were at the highest risk of death from road traffic accidents, although the majority of deaths occurred among young adults aged 20 to 60 years. However, the decline in the mortality of road traffic accidents among those aged below 20 years was less significant than that among adults.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, our study was restricted to pregnant women primarily from a low socioeconomic background with high burden of social, medical, and mental health problems. [41][42][43] Hence, readers should exercise caution when generalizing results from the present study to other populations. However, the consistency of our findings from studies done in the US and Japan suggest that FIRST-S may be useful for assessing stress-related sleep disturbances among Spanish speaking pregnant women.…”
Section: Discussionmentioning
confidence: 92%